Microencapsulation with Maillard Reaction Products to improve the oxidative stability of chia oil - Copado, Claudia Noelia (2019)
The oil obtained from the seeds of chia (Salvia hispanica L.) is a valuable plant source of omega-3 polyunsaturated fatty acids (PUFA). Chia oil’s high PUFA content makes it an interesting source for enriching foods with these essential fatty acids, but the oil’s high PUFA content also makes it susceptible to oxidation. Consequently, one of the most relevant challenges is to protect the oil from oxidative deterioration.